Words and sentences that are used in the language of japanese advertisement - Saudanbekova Sh Т; Amirbek, A Zh (Journal of Oriental Studies, 2016)
This paper presents an attempt to describe main lexical, syntactical, stylistic and some other specific features of Modern Japanese advertisement texts in the context of Japanese culture and mass ommunication theory.